Reducing dyspeptic symptoms in children: proton pump inhibitor vs. H2 receptor antagonist - Tien Budi Febriani; Titis Widowati; Mohammad Juffrie (Indonesian Pediatric Society Publishing House, 2014)
Background Dyspepsia is known as a leading cause of upper gastrointestinal tract morbidity. If left untreated, dyspepsia may become chronic. Dyspeptic symptoms manifest as epigastric pain, heartburn, nausea, hematemesis, or melena. Experimental studies have shown that omeprazole is more effective at reducing heartburn than ranitidine in adults. However, there have been few studies comparing the effects of proton pump inhibitors to Hz receptor antagonists for reducing dyspeptic symptoms in children. Objective To compare the effect of omeprazole with ranitidine for reducing dyspeptic symptoms . Methods We performed a double-blind randomized controlled trial (RCT) at Sardjito Hospital and three community h ealth centers in the Sleman District from June to November 2012. We recruited children aged 3-18 years with dyspepsia. Subjects were allocated into two groups using block randomization: the proton pump inhibitor (omeprazole) and the Hz receptor antagonist (ranitidine) groups. According to the groups, either omeprazole (0.4-0 .8 mg/kg/dose) or ranitidine (2-4 mg/kg/dose) , respectively, were taken twice daily for 5 days. Dyspepsia was clinically diagnosed using the new Rome III criteria. Both groups were monitored for 5 days to assess for a reduction of dyspeptic symptoms. Results Significantly more subjects in the omeprazole group recovered from dyspeptic symptoms than in the ranitidine group (RR= 4.87; 95%CI 1.5 to 15.3; P=0.005). Conclusion Omeprazole was 4.87 (95% CI 1.5 to 15.3) times better than ranitidine in reducing dyspeptic symptoms on children aged 3-18 years with dyspepsia.